Odpowiedzi

2010-03-03T21:09:51+01:00
1)9y - (7y + x) + (6x - 7y) =9y-7y-x+6x-7y=9y-14y+5x=-5y+5x=-5*3+5*(-2)=-15-10=-25
2)(6a - 8b - 0,7) - (6,9 + a - 5b) + 1,8=6a-8b-0,7-6,9-a+5b+1,8=5a-3b-5,8=5*0,2-3*0,1-5,8=1-0,3-5,8=-5,1
3)1/2abc - (4ab + 2abc) + (-bc + 5ab)=1/2abc-4ab-2abc-bc+5ab=-1 1/2abc+ab-bc=1/2*(-2)*1/2*(-4)+(-2)*1/2-1/2*(-4)=2+1+2=5
2010-03-03T21:11:13+01:00
1)
9y - (7y + x) + (6x - 7y) =
9y-7y-x+6x-7y =
-5y+5x =
-5*3+5*(-2) =
-15-10 =
-25


2)
(6a - 8b - 0,7) - (6,9 + a - 5b) + 1,8 =
6a-8b-0,7-6,9-a+5b+1,8 =
5a-3b-5,8 =
5*0,2-3*0,1-5,8 =
1-0,3-5,8 =
-5,1


3)
1/2abc - (4ab + 2abc) + (-bc + 5ab) =
½abc-4ab-2abc-bc+5ab =
-1½abc+ab-bc =
-1½*(-2)*½*(-4)+(-2)*½-½*(-4) =
-6-1+2 =
-5

14 5 14